Diffraction Control Methods of Extended Products’ Diameter; Materials Science Forum; Vol. 942 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance - Fedorov E. M. Evgeniy Mihailovich; Chicherina N. V. Natality Viktorovna; Tlusty J. Josev; Li Jianmin; Tuzikova V. S. Valeriya Sergeevna (2019, 2019)
Title screen